Assessment of trauma and injury severity score model for survival of trauma patients: a single centre experience - Gaikwad, Umesh Gaikwad; Wasnik, Nitin; Saxena, Divish; Akhtar, Murtaza (International Surgery Journal, 2018)
Background: Trauma and Injury Severity Score (TRISS) designed by Major Trauma Outcome Study (MTOS) in United States, is commonly used for outcome prediction in polytrauma patients. It determines the probability of survival (PS) of a patient from the Injury Severity Score (ISS) and Revised Trauma Score (RTS) using TRISS methodology. Methods: A total number of 136 patients presenting within 24 hours of trauma that were admitted were included in the study. The probability of survival was calculated using TRISS index (RTS, ISS, and age combination index). The predicted probability of survival and that of death among the study subjects were calculated using TRISS. A cut off 0.5 or lesser of TRISS score was taken as death and above 0.5 as survival status. Results: The mean TRISS among males and females were 86.12±21.76 and 79.49±27.70 and based on TRISS score the expected deaths were predicted to be 11.03%. But, in actual, the deaths were 23.52% showing a negative correlation with TRISS score in our set up thereby indicating a need to improve emergency facilities for trauma patients. Conclusions: TRISS methodology when applied to our setup predicted fewer deaths as compared to the actual deaths and also did not accurately predict the survival in the trauma patients.